Apoio social ao cuidador familiar do idoso dependente - Nardi, Edileuza de Fátima Rosina (2007)
The aging process can result in dependence and need for help and care, which can take place in the home and under the responsibility of the family, which, at the outset of the elderly's dependence, needs to restructure and to reorganize its role, redefining the responsibilities of each member. The task of caring includes the need for social support for the elderly and his/her caregiver, aiming at reducing the negative aspects of the care process, in addition to contributing to the improvement of the caregiver's quality of life and reflecting positively on the care rendered. This support can come from formal and informal sources, such as support groups, the family, non-governmental organizations, clergy, neighbors, friends, health and social assistance services. The present study aims to understand how formal and informal social support to the dependent elderly's family takes place. It is an exploratory-descriptive study, accomplished with 19 primary family caretakers of seniors dependent, in a small-sized city in southern Brazil. The collection of data was accomplished through home interviews, using a semi-structured interview script and the data was analyzed through thematic content analysis. The participant subjects of the study were constituted in their majority of wives anddaughters, married, aging, with low education level and low family income, living in multigenerational homes, taking care of dependent seniors for more than 4 years and performing household chores besides caring for the elderly patients. The care process was referred to by the participants as being a difficult and tiresome task, with a great deal of responsibility, dedication and requiring a lot of patience and willpower, influenced by the obligation owed and the retribution for the good moments lived with the elderly. As for the types of care given by the caretakers, there was predominance of activities related to the elderly's functional disability, being more frequent those linked to life maintenance - feeding, bathing, mobilization and transportation - and related to healing, such as administering medication. The greatest difficulties mentioned by the caregivers were actions that demanded physical effort, such as giving a bath and move the elderly, influenced by the lack of adaptation in the home, although six caregivers expressed no need for help or support to accomplish these tasks. Concerning social support, the same was noticed in varying intensities from both formal and informal support. In reference to informal social support, family members, community groups, neighbors and friends were mentioned; however, sons and daughters were most often cited. As formal social support, the caretakers referred to the basic health services, PSF team members, the local physical and speech therapy services, social assistance services and the local emergency service. The ACS, as the representative of formal health assistance, was the most mentioned, due to its bond with the family. Among the needs mentioned, the lack of financial means and orientation prevailed. Considering that the caregivers were aging, that caring caused physical, emotional and financial overload, and that the caregivers demanded information orientations for the caring process, it was concluded that both informal social support and formal support to the families were shown deficient. Therefore, it would be of fundamental importance to the care system to form a support network integrating formal and informal systems, seeking the promotion, prevention and recovery of the health of the elderly, caregiver and family.